Executive development : meeting the needs of top teams and boards - Jackson, Sheila (Journal of management development, 2003)
Numerous commentators emphasise that, to compete successfully in today'sever-changing environment, directors need to become more flexible andinnovative in their careers and in their day-to-day work (Beardwell and Holden,2001, p. 275; Longenecker and Fink, 2001, p.